Ø§ÙÙØ±ÙÙØ¨ ÙÙ Ø§ÙÙØºØ© Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ© ÙØ§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© : Ø¯Ø±Ø§Ø³Ø© ØªØÙÙÙÙØ© ØªÙØ§Ø¨ÙÙØ© - Zubaidi, Ahmad (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
Dalam pembelajaran bahasa kedua dikenal analisis kontrastif. Penelitian ini menggunakan pendekatan deskriptif komparatif, berjenis Library research. Data dihimpun dengan teknik dokumentasi. Adapun analisisnya menggunakan analisis konten dan analisis kontrastif. Penelitian ini menghasilkan temuan, bahwa terdapat sejumlah jenis frasa serta perbedaan dan persamaan antara frasa dalam BI dan BA. Frasa dalam BI : 1. Frasa setara, 2, frasa bertingkat, 3. Frasa terpadu. 4.Frasa benda setara, 5. Frasa benda bertingkat berstruktur M-D dan DM, 6. Frasa benda terpadu, 7. Frasa kerja berstruktur DM-MD, 8. Frasa sifat berstruktur DM-MD, 9. Frasa preposisi, 10. Frasa keterangan, frasa pronominal, 12. Frasa biasa, 13. Frasa idiomatic dan 14. Frasa ambigu. Sedang dalam BA: 1. Frasa Isnadi, 2. Frasa Idhofi, 3. Frasa bayani mencakup : frasa washfi, frasa taukidi, frasa badali, 4. Frasa âadadi, 5. Frasa jarri, 6. Frasa musyari, 7. Frasa munadi, 8. Frasa maushuli, 9. Frasa mazji, 10. Frasa tamyizi, 11. Frasa fiâli, 12. Frasa âathfi.In the second language learning, known contrastive analysis. This research uses a comparative descriptive approach, a library research type. The data were collected by documentation. As for its analysis, using content analysis and contrastive analysis. This research resulted in findings; that there are several types of phrases as well as the differences and similarities between phrases in Indonesian and Arabic. Phrases in Indonesian: 1. Exocentric phrase, 2. Endocentric phrase, 3. Integrated phrase. 4. Exocentric nominal phrase, 5. MD and DM structured nominal phrase, 6. Integrated nominal phrase, 7. DM-MD structured verbal phrase, 8. DM-MD structured adjectival phrase, 9. Prepositional phrase, 10. Adverbial phrase, 11. Pronominal phrase, 12. Simple phrase, 13. Idiomatic phrase and 14. Ambiguous phrase.Â  While in Arabic: 1. Isnadi phrase, 2. Idhofi phrase, 3. The bayani phrases include: washfi phrase, taukidi phrase, badali phrase, 4. Adadi phrase, 5. Jarri phrase, 6. Mushari phrase, 7. Munadi phrase, 8. Maushuli phrase, 9. Mazji phrase, 10. Tamyizi phrase, 11. Fili phrase, 12. Athfi phrase.